Fabrication of TiO2 nanofibre photoelectrode for photoelectrochemical cells - Nghia, Nguyen Van; Truong , Ngoc Khoa Nguyen; Hoang, Hieu Nhat (Hue University Journal of Science: Natural Science, 2022)
The TiO2 nanofibres (NFs), prepared with the electrospinning method, acted as the photoanode in a photoelectrochemical cell (PEC) for hydrogen generation. The fabrication parameters of Ti/PVP (polyvinylpyrrolidone) fibres were determined with the field-emission scanning electron microscopy (FE-SEM) method. The structure and morphology of the TiO2 fibres were characterized by using X-ray diffraction (XRD), FE-SEM, transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HR-TEM). The average diameter of the TiO2 fibre is 132 ± 16 nm. A three-electrode potentiostat was used to study the photoelectrochemical properties of the photoanode. The density photocurrent reached the saturation value of 80 mA·cm–2 at 0.2 V under the irradiation of a Xenon lamp.